2020
DOI: 10.19053/22160159.v11.n26.2020.10667
|View full text |Cite
|
Sign up to set email alerts
|

Criterios de idoneidad didáctica en una clase basada en el Lesson Study

Abstract: El objetivo de este trabajo es identificar los criterios de idoneidad didáctica usados por un grupo de profesores en un proceso de instrucción de una clase —diseño, implementación y reflexión/rediseño—, realizado en el marco de una experiencia de estudio de clases. Se utiliza la herramienta idoneidad didáctica para el análisis cualitativo. Se concluye que el grupo de profesores utiliza, de manera implícita, algunos de los componentes e indicadores de los criterios de idoneidad didáctica. En particular, se util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…In the case studied, first of all, we can recognize that the data show that both in phases 1 and 2, the working groups implicitly consider the DSC. This issue was considered a research premise has given to a considerable number of theoretical antecedents that have identified the implicit use of these DSCs in the reflections of teachers or future teachers when they reflect on the teaching practices of mathematics (Hummes et al, 2020;Morales-López & Font, 2019;Seckel et al, 2019Seckel et al, , 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case studied, first of all, we can recognize that the data show that both in phases 1 and 2, the working groups implicitly consider the DSC. This issue was considered a research premise has given to a considerable number of theoretical antecedents that have identified the implicit use of these DSCs in the reflections of teachers or future teachers when they reflect on the teaching practices of mathematics (Hummes et al, 2020;Morales-López & Font, 2019;Seckel et al, 2019Seckel et al, , 2021.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, different investigations on the training of mathematics teachers are observed, in which the DSC is used to analyze the implicit use of these criteria in the reflections on teaching and learning practices of mathematics (own or others) (Breda, 2020;Breda et al, 2021;Hummes et al, 2020;Morales-López & Font, 2019;Moreira et al, 2018;Seckel et al, 2019) and, on the other hand, researches are observed on training programs in which the DSC are used as content to explain to organize the teacher's reflection on their own practice, in undergraduate and postgraduate courses (Esqué de los Ojos Font et al, 2017;Giacomone et al, 2018;Godino et al, 2018;Hernández-García & Breda, 2022).…”
Section: Criteria Of Didactic Suitability In/for the Design Of Instru...mentioning
confidence: 99%
“…By treating teaching as an educational act, revealed in movements of individual and collective reflection, as realized in all stages of lesson study (Hummes et al, 2020;Murata, 2011;Ponte et al, 2016;Rincón & Fiorentini, 2017;Richit & Tomkelski, 2020), allowed the participants to more accurately gauge the scope of this activity. In addition, experiences in lesson study led them to understand how teacher action can enhance or support student development.…”
Section: Educational Actionmentioning
confidence: 99%
“…Por tanto, es de esperar que, en las fases de planificación, de observación, de reflexión y en la de rediseño orientada a la mejora, los participantes usen de manera implícita muchos de los indicadores y componentes de los ci para hacer valoraciones positivas de algunos aspectos de la experiencia realizada. Por tanto, en una experiencia de ec van a surgir consensos implícitos entre los participantes sobre aspectos que se valoran positivamente, los cuales se pueden reinterpretar en términos de indicadores y componentes de los ci, tal como se evidencia en Hummes, Breda y Seckel (2019) y en Hummes et al (2020).…”
Section: N1 N2 N3unclassified